Penyuluhan Tentang Khasiat Graptophyllum Pictum ( Daun Puding Hitam ) Bagi Kesehatan Tubuh Manusia - Rikomah, Setya Enti; Arifqi Afif Saputra; Anisa Agus; Mutiara Aulia Parmacita; Dwi Marshanda; Vhina Wulan Sundari (Gayaku Publisher, 2023)
The black pudding plant is a plant that is effective in treating various diseases. Black pudding contains alkaloids, saponins, tannins, glycolose, flavonoids, calcium olsalate, steroids and fat. Black leaves have chemical properties as an anti-inflammatory, laxative of urine, accelerates the cooking of boils, mild laxatives, softens the skin of the feet, softens the stool and deflates the stool. Therefore, this service aims to provide knowledge to the public about the important properties of the black pudding plant (Graptophyllum pictum). Activities carried out include education on human health for the community and students. This activity is expected to provide benefits for students and the community in increasing knowledge and understanding of the important properties of the black pudding plant (Graptophyllum pictum).